Estudo da prevalência de hemoglobina S em doadores de sangue na região de Santa Maria-RS e aconselhamento genético familiar - Giovelli, Letícia Loi (2009)
The Sickle Cell Anemia is the most common monogenic hereditary disease in the world. The cause of this disease is a changing point in the position six of the beta globin gene for hemoglobin, changing the glutamic acid by a valine, with consequent physical and chemical modification of the molecule and result in abnormal hemoglobin, called hemoglobin S (HbS). The sickle cell trait characterized the asymptomatic carriers, heterozygous (HbAS), which does not present the disease or have abnormalities in the number and shape of red blood cells. Carriers in this situation is very frequent, in Brazil can reach 1 to 5% of the general population and from 6 to 10% of African descent, and the greater importance of their diagnosis is for genetic counseling of the affected population. This study aimed to determine the prevalence of sickle cell trait blood donors in the region of Santa Maria, promoting a genetic counseling reporting on reproductive risks, compare the most widely used screening methods for the detection of Hb S in blood banks, quantify abnormal hemoglobin found through quantitative electrophoresis and confirmed by molecular analysis. The study of the prevalence of Hb AS in blood banks was carried out with the screening of 26,071 blood donors who presented to the banks of blood from the University Hospital of Santa Maria (HUSM), Charity Hospital Dr. Astrogildo of Azevedo and Health House. Genetic counseling was conducted through individual guidance with explanations about the condition of sickle cell trait and awareness of genetic risk. To compare the methods of screening for detection of Hb S was analyzed a total of 4,108 donors by the methods of solubility, gel-centrifugation Diamed ID-HbS and hemoglobin electrophoresis qualitative in cellulose acetate. Of the total donors, 88 (0.34%) had results changed with the presence of Hb S. In genetic counseling, 57 (85%) blood donors with sickle cell trait came to attend counseling. In the comparison of methodologies, 23 donors (0.56%) had Hb S and 2 donors (0.05%) had Hb C. The frequency for the presence of Hb S in blood donors by the electrophoresis of hemoglobin was 23 (0.56%), the solubility test was 22 (0.53%) and gel-centrifuge test was 20 (0.49%). The solubility test showed 95.6% sensitivity and gel-centrifuge test Diamed ID-HbS showed 86.9% sensitivity when compared with the electrophoresis of hemoglobin and both proved to be 100% specific. This study showed that the prevalence of 0.34% of Hb AS is a value found to be very close to the reality of the region to present a very significant number of donors tested. The solubility test showed good specificity and sensitivity demonstrating to be a good method of choice for application in screening of Hb S in blood donors.